(untitled) (London Journal of Engineering Research, 2023)
Vibrations in road vehicles, mainly from road defects, have a number of harmful effcts. Occupants may suffer health problems, while vehicle components may be mechanically damaged. These effects can reduce the life of components, cause failures and ultimately lead to vehicle breakdown. From a health point of view, back pain, liver injury and musculoskeletal problems are common, and body vibrations and shaking can negatively affect ride comfort. The greatest negative impact is caused by a small number of large, isolated road defects, which generate low frequency but high amplitude vibrations. Related to this, our study aims to develop and implement a vibration-based road quality measurement system capable of detecting and differencing these prominent road defects. The implemented device is universally applicable to passenger vehicles, can be constructed at low cost and is controllable from a touch screen. The system includes inertial and GPS sensors, and various feature extraction and sensor fusion methods were used to ne-tune the results. The system has been tested and validated under real measurement conditions using measurement data collected on public roads.